2022
DOI: 10.28982/josam.1080889
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus-19 pandemic and its impact on elective neurosurgical operations

Abstract: Background/Aim: The Coronavirus-19 (COVID-19) pandemic disrupted all planned, elective surgical procedures and appointment-based health services due to the decreased capacity of hospitals, healthcare professionals' focus on fighting the pandemic and efforts to protect patients, society and healthcare workers from the pandemic. The purpose of this study was to ascertain the perspective of patients on elective surgery, who applied to neurosurgery outpatient clinics at two different centers as clean and nonclean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Studies undertaken in the early phases of the stay-at-home orders reported decreasing volumes of elective neurosurgical operations [ 11 , 25 , 26 , 27 ]. Similarly, the quantity of neurosurgical traumas was also reported to be in a decline [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies undertaken in the early phases of the stay-at-home orders reported decreasing volumes of elective neurosurgical operations [ 11 , 25 , 26 , 27 ]. Similarly, the quantity of neurosurgical traumas was also reported to be in a decline [ 28 ].…”
Section: Discussionmentioning
confidence: 99%